Analysis of the Problems of Early Marriage on Islam in Krucil Sumber Durian Village, Probolinggo - Bashori Alwi; Sirojul Munir (Risalah, Jurnal Pendidikan dan Studi Islam, 2023)
This study describes the analysis of the problems of early marriage in Sumber Duren Village. Early marriage has been a long-standing phenomenon, but is now re-emerging on the surface. This study aims to determine the motive behind this phenomenon. This study uses a qualitative approach to the type of case study. The data was obtained through observation and interviews. There were fourteen informants in this study, consisting of village heads, KUA officials, parents and children involved in early marriages. Data analysis uses data collection, data reduction, data display, and conclusions. As for the research results obtained, there are four things that are problematic for the occurrence of early marriage in Sumber Duren Village, namely matchmaking, self-will, low economy, and tradition. Matchmaking is one of the causes of early marriage in Sumber Duren Village, and this is because by choosing a partner for their child, the parents feel calmer. The son's or daughter's own will also causes early marriage in Sumber Duren Village. This happens for several reasons: feeling that they already understand marriage, not wanting to burden their parents, and pressure from the couple. Next is the economic factor that causes early marriage in Sumber Duren Village. The family's difficult economic conditions can trigger parents' mindsets to marry off their sons and daughters. It is intended that the financial problems experienced can be overcome. The ancestral tradition of marrying at an early or relatively young age is also one of the causes of early marriage in Sumber Duren Village. Most parents consider that early marriage is a positive and common thing, even considering that early marriage is an ancestral tradition that must be preserved and ignore the rules in marriage.